2020
DOI: 10.3390/pr8040404
|View full text |Cite
|
Sign up to set email alerts
|

Forward Osmosis: A Critical Review

Abstract: The use of forward osmosis (FO) for water purification purposes has gained extensive attention in recent years. In this review, we first discuss the advantages, challenges and various applications of FO, as well as the challenges in selecting the proper draw solution for FO, after which we focus on transport limitations in FO processes. Despite recent advances in membrane development for FO, there is still room for improvement of its selective layer and support. For many applications spiral wound membrane will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 219 publications
(328 reference statements)
0
33
0
Order By: Relevance
“…Forward osmosis (FO) is an osmotically driven separation process where the higher osmotic potential of the draw solution governs the water through a tight (comparable to RO) semipermeable membrane. To achieve an effective separation, not only does the feed side have to have a thin active layer, but the whole membrane has to be thin to mitigate dilutive internal concentration polarization [ 32 , 33 ]. In spite of some intrinsic advantages, the practical implementation of FO has not caught up with the vast number of scientific publications to date [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Forward osmosis (FO) is an osmotically driven separation process where the higher osmotic potential of the draw solution governs the water through a tight (comparable to RO) semipermeable membrane. To achieve an effective separation, not only does the feed side have to have a thin active layer, but the whole membrane has to be thin to mitigate dilutive internal concentration polarization [ 32 , 33 ]. In spite of some intrinsic advantages, the practical implementation of FO has not caught up with the vast number of scientific publications to date [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…An additional benefit of FO is a phenomenon called retarded forward diffusion of solutes [36]. In this phenomenon, the reverse salt flux in FO processes impedes the pore diffusion of feed solutes, leading to the high rejection of feed solutes [29,36]. As mentioned earlier, when a high osmotic pressure gradient is obtained across the membrane, sufficient water flux and recovery can be achieved [15,34].…”
Section: Advantages Of Fo Membranesmentioning
confidence: 97%
“…Another benefit of FO that is tied to not requiring hydraulic pressure is a reduction of fouling. Recent studies have demonstrated that a lack of applied hydraulic pressure and optimization of the system's hydrodynamics can lead to less fouling and the higher reversibility of fouling [15,[29][30][31][32]. Due to the low flux that can be obtained in FO, there is more opportunity for low fouling [28,32,33].…”
Section: Advantages Of Fo Membranesmentioning
confidence: 99%
“…This method provides additional resolution and accuracy in determining the osmotic pressure. Knowing the individual osmotic pressures, π(Cm) and π(Cs), the PRO osmotic pressure difference can be calculated by solving for the difference between both terms, as seen by Equation (7). For FO mode, the terms on the right-hand side of Equation 7are reversed.…”
Section: Prediction Of the Osmotic Pressure Difference δπMmentioning
confidence: 99%